Bornyl Diphosphate Synthase From Cinnamomum burmanni and Its Application for (+)-Borneol Biosynthesis in Yeast - Ma, Rui; Su, Ping; Guo, Juan; Jin, Baolong; Ma, Qing; Zhang, Haiyan; Chen, Lingli; Mao, Liuying; Tian, Mei; Lai, Changjiangsheng; Tang, Jinfu; Cui, Guanghong; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
(+)-Borneol is a desirable monoterpenoid with effective anti-inflammatory and analgesic effects that is known as soft gold. (+)-bornyl diphosphate synthase is the key enzyme in the (+)-borneol biosynthesis pathway. Despite several reported (+)-bornyl diphosphate synthase genes, relatively low (+)-borneol production hinders the attempts to synthesize it using microbial fermentation. Here, we identified the highly specific (+)-bornyl diphosphate synthase CbTPS1 from Cinnamomum burmanni. An in vitro assay showed that (+)-borneol was the main product of CbTPS1 (88.70% of the total products), and the Km value was 5.11±1.70 µM with a kcat value of 0.01 s-1. Further, we reconstituted the (+)-borneol biosynthetic pathway in Saccharomyces cerevisiae. After tailored truncation and adding Kozak sequences, the (+)-borneol yield was improved by 96.33-fold to 2.89 mg·L-1 compared with the initial strain in shake flasks. This work is the first reported attempt to produce (+)-borneol by microbial fermentation. It lays a foundation for further pathway reconstruction and metabolic engineering production of this valuable natural monoterpenoid.